The chloride channel CFTR is not required for cyst growth in an ADPKD mouse model. Issue 10 (2nd September 2021) - Talbi, Khaoula; Cabrita, Inês; Kraus, Andre; Hofmann, Sascha; Skoczynski, Kathrin; Kunzelmann, Karl; Buchholz, Bjoern; Schreiber, Rainer
Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is characterized by the development of bilateral renal cysts which enlarge continuously, leading to compression of adjacent intact nephrons. The growing cysts lead to a progressive decline in renal function. Cyst growth is driven by enhanced cell proliferation and chloride secretion into the cyst lumen. Chloride secretion is believed to occur mainly by the cAMP‐activated cystic fibrosis transmembrane conductance regulator (CFTR), with some contribution by the calcium‐activated chloride channel TMEM16A. However, our previous work suggested TMEM16A as a major factor for renal cyst formation. The contribution of CFTR to cyst formation has never been demonstrated in an adult ADPKD mouse model. We used mice with an inducible tubule‐specific Pkd1 knockout, which consistently develop polycystic kidneys upon deletion of Pkd1. Cellular properties, ion currents, and cyst development in these mice were compared with that of mice carrying a co‐deletion of Pkd1 and Cftr. Knockout of Cftr did not reveal any significant impact on cyst formation in the ADPKD mouse model. Furthermore, knockout of Cftr did not attenuate the largely augmented cell proliferation observed in Pkd1 knockout kidneys. Patch clamp analysis on primary renal epithelial cells lacking expression of Pkd1 indicated an only marginal contribution of CFTR to whole cell Cl − currents, which were clearly dominated by calcium‐activated TMEM16A currents. In conclusion, CFTR does not essentially contribute to renal cyst formation in mice caused by deletion of Pkd1. Enhanced cell proliferation and chloride secretion is caused primarily by upregulation of the calcium‐activated chloride channel TMEM16A.